2014
DOI: 10.1080/15374416.2014.900720
|View full text |Cite
|
Sign up to set email alerts
|

Marital Quality Spillover and Young Children's Adjustment: Evidence for Dyadic and Triadic Parenting as Mechanisms

Abstract: Research has evidenced support for the spillover model, which posits that parents' marital functioning influences child adjustment by eroding parenting and coparenting in dyadic (mother–child and father–child) and triadic (mother–father–child) contexts. However, prior work has not simultaneously investigated dyadic and triadic parenting as mechanisms of spillover. Furthermore, although evidence indicates that the marital system affects child adjustment by influencing parents' behavior, research has not explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 40 publications
7
68
1
5
Order By: Relevance
“…This study found a significant connection between the roles of both family resilience and marital satisfaction on children's behavioral adjustment, while taking into account mothers' perceived stress-related factors. The results are consistent with research on parenting stress and children's adjustment in which higher levels of perceived stress are related to children's behavioral difficulties (Ozeki & Knowles, 2009;Stroud et al, 2015).…”
Section: Children's Behavioral Adjustmentsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found a significant connection between the roles of both family resilience and marital satisfaction on children's behavioral adjustment, while taking into account mothers' perceived stress-related factors. The results are consistent with research on parenting stress and children's adjustment in which higher levels of perceived stress are related to children's behavioral difficulties (Ozeki & Knowles, 2009;Stroud et al, 2015).…”
Section: Children's Behavioral Adjustmentsupporting
confidence: 89%
“…The connection between marital satisfaction and children's adjustment has been examined in other contexts (Stroud, Meyers, Wilson, & Durbin, 2015). For instance, researchers have found that marital distress has been associated with children's emotional and behavioral adjustment (Fishman & Meyers, 2000;Katz & Gottman, 1993).…”
Section: Marital Satisfactionmentioning
confidence: 99%
“…Substantial research on the general population has documented that a high level of couple conflict and the use of maladaptive conflict resolution strategies by parents negatively impacts child functioning and behavior problems (e.g., McCoy, George, Cummings, & Davies, 2013; Stroud, Meyers, Wilson, & Durbin, 2014). On the other hand, there is also evidence that contexts of high child-related challenges put parents at risk for frequent, intense, and unresolved couple conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the parent–child dyad, the marital relationship has increasingly been recognized as an important factor in child development (Stroud, Meyers, Wilson, & Durbin, ). The adverse effect of exposure to marital conflict on child internalizing and externalizing behaviors has been well documented (Bornovalova et al., ).…”
Section: Introductionmentioning
confidence: 99%